2007
DOI: 10.1583/06-2050.1
|View full text |Cite
|
Sign up to set email alerts
|

Angio-Seal in Antegrade Endovascular Interventions: Technical Success and Complications in a 55-Patient Series

Abstract: ¤ ¤Purpose: To assess the technical success and complications of Angio-Seal vascular closure device in antegrade common femoral artery (CFA) punctures.Methods: Over a 14-month period, 55 patients (37 men; age range 37-94 years) underwent antegrade CFA Angio-Seal placement at a single center; the clinical data and angiograms were reviewed retrospectively. A total of 56 antegrade CFA punctures were made for hemostasis; 6-F Angio-Seal devices (40 model STS and 12 model VIP) were deployed in 52 CFAs, and 8-F Angio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 15 publications
0
17
0
Order By: Relevance
“…Arterial closures with the 8-F AngioSeal or Perclose ProGlide have been safe and effective in achieving immediate hemostasis in fully anticoagulated patients after peripheral interventional procedures using an antegrade or a retrograde approach. [5][6][7][8][9][10][11] These devices, however, have a small but significant number of disadvantages. For example, suture-mediated devices suffer from imprecise placement of suture, with consequent inadequate closure and narrowing of the vessel, 12 or groin infections that require drainage of the abscess, removal of the suture, and repair of the vessel.…”
Section: Discussionmentioning
confidence: 99%
“…Arterial closures with the 8-F AngioSeal or Perclose ProGlide have been safe and effective in achieving immediate hemostasis in fully anticoagulated patients after peripheral interventional procedures using an antegrade or a retrograde approach. [5][6][7][8][9][10][11] These devices, however, have a small but significant number of disadvantages. For example, suture-mediated devices suffer from imprecise placement of suture, with consequent inadequate closure and narrowing of the vessel, 12 or groin infections that require drainage of the abscess, removal of the suture, and repair of the vessel.…”
Section: Discussionmentioning
confidence: 99%
“…For the Angio-Seal device, there have been only 3 case series discussing ¤ ¤ 9 Minor complications (2 hematomas) occurred in 3.6% of the patients who underwent device insertion. Mukhopadhyay et al 10 studied 21 antegrade punctures and found a 9.4% complication rate, which included a hematoma and 1 case of ischemia.…”
Section: Discussionmentioning
confidence: 99%
“…Perclose, using two 6-F devices for "preclosure, " and Prostar XL are particularly well positioned in this respect, and there are some excellent descriptive series showing a high success rate, despite use of sheaths up to 24 F. 7 There is increasing interest in closure of antegrade femoral punctures, and a number of studies have described use of many of the previously mentioned devices, albeit offlabel. [8][9][10] Similarly, there is additional interest in using VCDs off-label for the brachial approach, although the limited depth of the arteriotomy should exclude a number of devices from consideration. 11 Overall, I am aware of a half dozen VCDs making their way through bench, animal, and human testing, and I expect to have a number of other devices to discuss in the next installment of this column.…”
Section: The Crystal Ballmentioning
confidence: 99%